2020
DOI: 10.1016/j.jid.2019.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Inflammatory Phenotype in Residual Psoriatic Plaques in Patients on Effective Biologic Therapy

Abstract: Many psoriasis patients treated with biologics do not achieve total skin clearance. These patients possess residual plaques despite ongoing biologic treatment. To elucidate mechanisms of plaque persistence despite overall good drug response, we studied 50 subjects: psoriasis patients with residual plaques treated with one of three different biologics, untreated patients, and healthy controls. Skin biopsies from all subjects were characterized using three methods: mRNA expression, histology, and FACS of hematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…6,7 In agreement with other reports, the secukinumab-resistant PSO plaque showed a high expression of IL-17A. 8,9 The patient's paradoxical LP lesion did not show any IL-17A expression. Interestingly, the secukinumab-resistant PSO plaque showed some IL-4 expression, a cytokine, which is normally absent in PSO lesions.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…6,7 In agreement with other reports, the secukinumab-resistant PSO plaque showed a high expression of IL-17A. 8,9 The patient's paradoxical LP lesion did not show any IL-17A expression. Interestingly, the secukinumab-resistant PSO plaque showed some IL-4 expression, a cytokine, which is normally absent in PSO lesions.…”
supporting
confidence: 90%
“…8,9 Such elevated cytokine levels have been attributed to the persistence of CD3 + T cells, innate lymphoid cells and mast cells. 8,9 Although our findings are based on a single case study, they indicate some distinct immunological features of paradoxical LP and treatment-resistant PSO skin under anti-IL-17A blockade compared with spontaneous LP and untreated PSO skin. However, clinical presentation and histological features were similar within each skin disorder (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on residual psoriasis after the use of biologics revealed a decrease in keratinocyte proliferation. However, the percentage of IL-17A-producing CD103 + TRM was not significantly reduced after the treatments [92]. Similarly, a new normal in the persistence of IL-17A-producing TRM with CCR6 and IL-23R expression in the resolved skin has been established [62,80].…”
Section: Skin T Rm In the Pathogenesis Of Psoriasismentioning
confidence: 95%
“…Furthermore, CD8 + T cells producing IL-17 and CD4 + T cells producing IL-22 remain in resolved lesions and can be stimulated to produce psoriasis-related cytokines even after treatment with biologics such as infliximab for several years [51]. Interestingly, the effect on the presence of TRMs of treatment with different biological drugs has also been studied and, so far, no difference in the number of CD103 + cells in residual psoriatic plaques has been shown [116]. The presence of IL-17A-producing CD8 + CD103 + TRMs in the epidermis has been found to contribute to the prognosis of psoriasis [52].…”
Section: Psoriasismentioning
confidence: 99%